2015
DOI: 10.1111/fme.12142
|View full text |Cite
|
Sign up to set email alerts
|

Upstream migration of amphidromous gobies of La Réunion Island: implication for management

Abstract: Diadromous species of tropical islands face numerous anthropogenic disturbances. Understanding how these disturbances affect the population dynamic of these species is important to develop ecologically based management measures. The upstream migration dynamics of two amphidromous gobies, Sicyopterus lagocephalus (Pallas) and Cotylopus acutipinnis (Guichenot), was described using intensive fishway monitoring (28 sampling dates over 1.5 years, 13 000 S. lagocephalus, 23 000 C. acutipinnis captured). Migration pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 52 publications
0
26
1
Order By: Relevance
“…Moreover, the ecological advantage of the better climbing performance of S. lagocephalus compared to C. acutipinnis is probably exacerbated by the dams and weirs that have been constructed during the past decades in Réunion Island. Most of these barriers are much higher than the experimental ramps of this study and/or with a longitudinal slope steeper than 45° (DEAL, ; Lagarde et al ., ). The selective pressure of these anthropogenic barriers can consequently be beyond the climbing performance of most C. acutipinnis juveniles and, as a result, add a threat to the sustainability of this endemic species population.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the ecological advantage of the better climbing performance of S. lagocephalus compared to C. acutipinnis is probably exacerbated by the dams and weirs that have been constructed during the past decades in Réunion Island. Most of these barriers are much higher than the experimental ramps of this study and/or with a longitudinal slope steeper than 45° (DEAL, ; Lagarde et al ., ). The selective pressure of these anthropogenic barriers can consequently be beyond the climbing performance of most C. acutipinnis juveniles and, as a result, add a threat to the sustainability of this endemic species population.…”
Section: Discussionmentioning
confidence: 97%
“…The hypotheses explaining these displacements are generally related to fish competition for habitat (Fitzsimons & Nishimoto, 1990), extreme climatic events that induce fish flushing (Lagarde et al, 2015;Smith & Kwak, 2014a), or reproduction (Koster et al, 2013;Lord et al, 2011). The hypotheses explaining these displacements are generally related to fish competition for habitat (Fitzsimons & Nishimoto, 1990), extreme climatic events that induce fish flushing (Lagarde et al, 2015;Smith & Kwak, 2014a), or reproduction (Koster et al, 2013;Lord et al, 2011).…”
Section: Moreover the Steep Rivers With High Flow Velocity Of La Réumentioning
confidence: 99%
“…Downstream migration can be related to movement of adult fish towards spawning grounds close to the marine environment. For instance, Lagarde, Teichert, Boussarie, Grondin, and Valade (2015) documented upstream movements of Sicyopterus lagocephalus adults that were probably recolonising their initial habitats after having been washed down during flood events. However, fish movements between river reaches are not exclusively linked to reproduction, but can also be related to foraging behaviour or competition for food and/or territory, or caused by involuntary displacement due to periodic disturbances, such as cyclonic floods .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis has been developed by Lord, Tabouret, Claverie, Pécheyran, and Keith (2011) based on the variations in otolith elemental composition in adults of Sicyopterus lagocephalus and S. aiensis in Vanuatu rivers. However, a recent study focused on the migration of adults and juveniles of two Sicydiinae species, including S. lagocephalus, in tropical rivers (Lagarde, Teichert, Boussarie, Grondin, & Valade, 2015), suggested that the downstream displacements of adults depend solely on hydrological disturbances during cyclonic floods. If spawning location is not intended to reduce the time spent by larvae in freshwater, the only strategy for reaching the ocean more rapidly would be that larvae drift faster, mainly during periods of elevated river discharge.…”
mentioning
confidence: 99%